Causative antigens of humidifier lung in vapor from a humidifier: A case report. (2023) - Shimoda, Masafumi; Morimoto, Kozo; Hosoya, Makiko; Osugi, Asami; Mitarai, Satoshi; Tanaka, Yoshiaki; Fujiwara, Keiji; Yoshimori, Kozo; Ohta, Ken
Abstract: A 68-year-old man exhibited fever and cough three weeks prior to hospital admission after three months of ultrasonic humidifier usage. Chest computed tomography showed bilateral ground-glass opacities, lymphocyte levels in the bronchoalveolar lavage fluid were elevated (60.8%), and the histological examination of a transbronchial lung biopsy showed lymphocytic alveolitis. He gradually improved without medication after he stopped using the humidifier. Accordingly, humidifier lung was the diagnosis. Humidifier water and vapor collected from the patient's humidifier were investigated. Humidifier vapor was obtained by collecting the condensed moisture. Laboratory examinations exhibited gram-negative rods and a high concentration of endotoxin and (1 → 3)-β-D-glucan in both vapor and water. The serum-precipitating antibodies showed a stronger reaction against humidifier vapor than against humidifier water. 16S rRNA metagenomic analysis revealed a high percentage of sequences of Spirosoma lacussanchae and Sphingomonas spp. in both the humidifier vapor and water. The percentages of sequence reads were lower in humidifier vapor than in water; conversely, sequences of Pseudomonas spp. and Allorhizobium-Neorhizobium-Pararhizobium-Rhizobium were more concentrated in the humidifier vapor than in humidifier water. Although the reason for the different bacterial ratios between humidifier vapor and water is uncertain, the bacteria that were more concentrated in humidifier vapor than in humidifier water might have been the causative antigen underlying the humidifier lung diagnosis. This is the first report to indicate the presence of causative antigens in humidifier vapor.